Improving selection practices of subcontractors on building construction project in Nigeria - Muhammad, Jibril Adamu (2016)
Subcontracting in Nigeria has extensively been used in the construction industry. It allows main contractor to employ a minimum workforce in construction projects and promotes specialization. The relationship between the main contractor and the subcontractors differ from one project to another. However, improper selection of subcontractors might lead to many problems during work pogress. This research focuses on improving subcontractor selection practices by the main contractors on building construction project in Nigeria. The objectives of the research were to identify the factors causing adversarial relationship between the main contractor and the subcontractor, identify significant factors used for subcontractors selection by the main contractor, and recommend ways for improving a better selection practices of subcontractors by the main contractor. The quantitative approach was used to obtain information from contractors (category A) for subcontractors selection practices. The data from the questionnaires were collected and analysed using Statistical Package for Social Science (SPSS) version 22.0. The data gathered was f converted into the form of percentages, tables, and charts. The results of the indings shows that incompetency of the subcontractor and non adherence of the subcontractor to the time schedule where among the factors causing adversarial relationship between the main contractor and the subcontractor, while providing dequate inormation to the subcontractor and speciality in certain type of work were ranked top for the factors used for subcontractors selection by the main contractor. In addition avoiding collection of kickbacks in construction and use of skilled labour force were the most significant ways to improve subcontractors selection practices by the main contractor. Subcontractors selection plays a vital role in the overall success of any construction project in order to get best results in te1ms of cost, time, and quality for the projects